Acute Myelomonocytic Leukemia Presenting as Perianal Pain. (27th November 2018) - Iqbal, Syma; Walcott, James; Chan, Stephen
Abstract : Extramedullary involvement of the gastrointestinal tract (GIT) is a rare entity as most patients present with lymphoreticular organ involvement. Its detection and diagnosis can be extremely challenging, as these patients would present with unusual clinical symptoms. We diagnosed and managed a patient with leukemic infiltration of GIT who presented with perianal pain. Prompt use of MRI played an important role in detecting underlying pathology, and effective tissue sampling confirmed the diagnosis. This resulted in overall successful management of the patient.